A case of gastrointestinal mucormycosis - Adhira, B; Vinod, V S; Nikitha, K (Indian Journal of Case Reports, 2026)
We report a case of a 74-year-old asthmatic lady on inhalers who came with acute exacerbation of bronchial asthma with no evidence of hypercarbia or acidosis and during her course in hospital stay, she developed an acute onset of abdominal distension due to intestinal obstruction. She was extensively evaluated and was finally diagnosed with gastrointestinal mucormycosis. Primary gastric mucormycosis is a rare but potentially lethal fungal infection due to the invasion of Mucorales into the gastrointestinal mucosa. Being a rare entity, the diagnosis is most often overlooked. The importance of this case is that a high index of suspicion is required for early diagnosis and management of the disease, and the mortality is very high, particularly in immunocompromised patients.